Ultrasound-Assisted Extraction of Phenolic Compounds from Moroccan Lavandula stoechas L.: Optimization Using Response Surface Methodology - Yassine Ez zoubi; Mouhcine Fadil; Dalila Bousta; Abdelhakim El Ouali Lalami; Mohammed Lachkar; Abdellah Farah (Journal of Chemistry)
Secondary plant metabolites, in particular phenolic compounds, are characterized by great diversity in the plant kingdom and are widely used in the medical and industrial fields. The extraction of these compounds represents a critical step, and the differences in extraction conditions strongly affect the yields and the total concentrations of polyphenols in the extracts. In this way, the objective of the present study was to optimize the extraction parameters of the polyphenols from Lavandula stoechas using the extraction technique assisted by ultrasound. Yield and the total concentration of polyphenols have been optimized, taking into account three variables, the extraction time (min), the ethanol concentration (%), and the solvent/extract ratio (ml/g). The optimum extraction yield (31.88%) was obtained by ensuring the following parameters: an ethanol concentration of 40%, a liquid/solid ratio of 30 ml/g, and a time processing of 32.62 min. The maximum concentration of total polyphenols (190.14 mg gallic acid equivalents (GAE)/g) was obtained after 21.5 min of extraction, with a liquid/solid ratio of 30 ml/g and a concentration of ethanol at 40%. In order to obtain the maximum yield (24.9%) and the total concentration of polyphenols (190.14 mg GAE/g) simultaneously, the following parameters must be adjusted: an extraction time of 21.5 min, a liquid/solid ratio of 30 ml/g, and a concentration of ethanol at 40%. The experimental values of the yield and the total concentration of the polyphenols were in good agreement with the predicted values, which suggests that the ultrasonic extraction model adopted in this study is validated.